Evaluating conceptual models of landscape change - Brudvig,LA; Leroux,SJ; Albert,CH; Bruna,EM; Davies,KF; Ewers,RM; Levey,DJ; Pardini,R; Resasco,J (Ecography, 2016)
A variety of landscape models are used to conceptualize and interpret human impacts on ecosystems and their biodiversity. The simplest, a ‘patch-matrix’ model, is rooted in island biogeography theory and assumes a dichotomy between generic, easily-defined habitat patches and a surrounding matrix that is completely inhospitable. This dichotomy between patch and matrix habitats has been recently relaxed, with the ‘continuum’ model taking this relaxation to its extreme and logical endpoint – a species-based model with no a priori definition of habitat or matrix, but rather focusing on ecological gradients. Yet, because few empirical comparisons of these bookending models exist, we lack understanding of their relative utility or the merits of hybrid approaches that combine attributes of patch-matrix and continuum models. To guide such considerations, we first develop a decision-making framework for the application of patch-matrix, continuum, and hybrid models. The framework takes into account study objectives, attributes of the landscape, and species traits. We then evaluate this framework by empirically comparing how continuum, patch-matrix, and hybrid models explain beetle distributions across two contrasting fragmented landscapes, for species differing in trophic level and habitat specificity. Within the Hope River Forest Fragmentation Project, a system with strong landscape contrast and distinct (‘hard’) structural edges between forest fragments and grassland, we find broad support for hybrid models, particularly those incorporating surrounding landscape structure. Conversely, within the Wog Wog Habitat Fragmentation Experiment, a system with weak landscape contrast and ‘soft’ structural edges between natural and plantation forest, we find co-support for continuum and hybrid models. We find no support in either system for patch-matrix, relative to continuum and hybrid models. We conclude by considering key questi